Pemanfaatan ICT dalam Kegiatan Pembelajaran Matematika di Sekolah - Puji Chairu Fadhilah; Intan Udana Siahaan (Interdisciplinary Explorations in Research Journal, 2023)
Education is something that a country needs to develop its resource potential. Indonesia has made education a field where someone can become a human being with morals and nobility. Education in Indonesia definitely experiences changes every year. It is hoped that these changes will make education in Indonesia better. Currently the most discussed trend is the change in the 2013 curriculum to an independent curriculum. Today's students are able to spend their time interacting with technology. Apart from that, the independent curriculum has also provided ICT learning to students. ICT is Information Communication and Technology or previously known as ICT. In this case, teachers must also make more use of technology to convey learning material to students. ICT can be used by teachers for an aspect of their needs as teachers. Starting from creating learning plans, learning processes, learning books and even evaluating learning, teachers can use ICT. Pendidikan adalah sesuatu yang dibutuhkan oleh sebuah negara untuk mengembangkan potensi sumber daya yang dimilikinya. Indonesia menjadikan pendidikan sebagai ladang dimana seseorang dapat menjadi manusia yang berakhlak dan berbudi pekerti luhur. Pendidikan di Indonesia pasti mengalami perubahan setiap tahunnya. Perubahan-perubahan tersebut diharapkan dapat membuat pendidikan di Indonesia menjadi lebih baik. Saat ini yang sedang ramai diperbincangkan adalah perubahan kurikulum 2013 menjadi kurikulum mandiri. Siswa saat ini dapat menghabiskan waktu mereka untuk berinteraksi dengan teknologi. Selain itu, kurikulum mandiri juga telah memberikan pembelajaran TIK kepada siswa. ICT adalah Information Communication and Technology atau yang sebelumnya dikenal dengan TIK. Dalam hal ini, guru juga harus lebih memanfaatkan teknologi untuk menyampaikan materi pembelajaran kepada siswa. TIK dapat digunakan oleh guru untuk aspek kebutuhannya sebagai pengajar. Mulai dari membuat rencana pembelajaran, proses pembelajaran, buku pembelajaran bahkan evaluasi pembelajaran, guru dapat menggunakan TIK.